The Interaction Between Venous Thromboembolism and Socioeconomic Status on the Risk of Disability Pension - Jørgensen H; Horváth-Puhó E; Laugesen K; Braekkan SK; Hansen JB; Sørensen HT (Clinical Epidemiology, 2022)
Helle Jørgensen,1– 3 Erzsébet Horváth-Puhó,2 Kristina Laugesen,2 Sigrid K Braekkan,1,3 John-Bjarne Hansen,1,3 Henrik Toft Sørensen2 1Thrombosis Research Center (TREC), Department of Clinical Medicine, UiT, The Arctic University of Norway, Tromsø, Norway; 2Department of Clinical Epidemiology, Department of Clinical Medicine, Aarhus University Hospital and Aarhus University, Aarhus, Denmark; 3Division of Internal Medicine, University Hospital of North Norway, Tromsø, NorwayCorrespondence: Helle Jørgensen, Email helle.jorgensen@uit.noBackground: Venous thromboembolism (VTE) is associated with increased risk of disability pension. How socioeconomic status (SES) impacts the risk of disability pension after a VTE is unknown. The aim of this nationwide population based cohort study to investigate the interaction between SES and incident VTE on the risk of subsequent disability pension.Methods: Using Danish national medical and administrative databases, we established a nationwide cohort of 41,781 individuals aged 25– 65 years with incident VTE during 1995– 2016 and a comparison cohort (n=208,905) from the general population matched on year of birth, sex, and calendar year of VTE. We computed incidence rates (IRs) as the number of disability pension events per 1000 person-years at risk and measured the interaction between VTE and levels of SES (high, medium, low) on an additive scale by calculating interaction contrasts (difference in IR difference).Results: Among individuals with high SES, the disability pension IR per 1000 person-years was 5.4 (95% CI: 4.8– 6.1) in the VTE cohort and 1.6 (95% CI: 1.5– 1.7) in the comparison cohort (IR difference 3.8). The corresponding disability pension IR in individuals with low SES was 55.1 (95% CI: 52.1– 58.1) in the VTE cohort and 26.1 (95% CI: 25.1– 27.1) in the comparison cohort (IR difference 24.0). An interaction contrast of 25.1 indicated that interaction accounted for 45.6% (25.1/55.1) of the disability pension IR in individuals with VTE and low SES.Conclusion: SES and VTE interact to increase the risk of disability pension after VTE beyond their independent effects.Keywords: education, employment, income, deep-vein thrombosis, pulmonary embolism, burden of illness